Study on Growth Quality of GaN Deposition on Nanopillar-Patterned Substrates: Microstructure Characterization and Crystalline Quality Optimization - Li, Lianxin; Gao, Tinghong; Chen, Qian; Huang, Jin (Crystal growth & design, 2024)
The preparation of gallium nitride (GaN) film materials has significant importance in the semiconductor and thermoelectric sectors, serving as essential core materials for chips, power supply, and communication applications. The production of GaN thin films with reduced defect density has emerged as a significant and continuous subject of research. This work investigated the deposition process of GaN thin films on an aluminum nitride nanopattern substrate via molecular dynamics simulation. A comparison was made between the deposition process on the nanopatterned and unpatterned substrates. Additionally, the impact of the substrate temperature and nanopillar radius on the quality of the thin film was examined. Results demonstrate that the use of a nanopillar pattern on the substrate facilitates the acquisition of the deposited film with a larger number of wurtzite structures and a reduced presence of dislocations. In contrast to the persistent and extensive dislocations formed in the thin films on an unpatterned substrate, the dislocations present in the thin films on a patterned substrate exhibit shorter lengths and more complexity. By appropriately elevating the temperature of the substrate, it is possible to effectively decrease the complexity of the atomic structure and enhance the thin film density. The correlation between the stress and the temperature of the thin film deposited on the patterned substrate is weak. The deformation of nanopillars with a too small radius can cause the deposited atoms to move into the nanovoid, aggravating the irregularity of the thin film surface and the volume of defects. Moreover, the excessive size of the nanopillar at which the surface area of the substrate approaches that of an unpatterned substrate can increase the occurrence of dislocations in the deposited film. This observation implies that the nanovoid ratio inside the nanopillar has a substantial impact on the deposition quality of the thin film. This study focuses on the deposition of GaN films on substrates with nanopatterns at the nanoscale, assesses the impact of nanopatterning degree on the growth quality of film, and acquires data on the temperature range and structural characteristics of high-quality films exhibiting high density and few dislocations.